PKM Strategi Penguatan Literasi Digital Kritis untuk Pembinaan Perempuan di Lapas Kota Pontianak - Rahmaniah, Syarifah Ema; Syarmiati, Syarmiati; Musa, Dahniar Th.; Marini, Marini; Alamri, Annisa Rizqa (GUYUB: Journal of Community Engagement, 2023)
Prison women are a group of people who are trained so that they do not repeat crimes when they reintegrate into society. Therefore, we conducted Tular Reason education activities for female Pontianak prison residents. The aim of the Tular Nalar digital literacy training at the Pontianak City women's prison is to (1) increase critical awareness to avoid crimes originating in the media, such as hoax traps and fraud, as well as incitement, hate speech, etc. (2) Provide the ability to check simple facts using several methods and tools. (3) Become a digital literacy agent in their environment. The activity participants are residents of the Pontianak Women's Penitentiary, most elderly. This activity was attended by 50 older women in prisons consisting of 45 prison residents and five prison officers. The participants were divided into five groups, each accompanied by one facilitator. The facilitators used the activity implementation guide module for the facilitator and the implementing team, templates of training props such as Stickers, Flyers, etc., which can be adjusted according to needs. The material presented to the participants included: (1) Understanding the basics of anti-hoax advocacy. (2) Understanding how to identify hoaxes, (3) Discussing digital fraud, (4) Discussing hate speech. The stages of the activity are using presentations, video screenings, and group discussions, practicing checking news hoaxes/facts, and filling out questionnaires to find out the participants' understanding accompanied by facilitators. The activity results were that the participants could identify hoaxes from the teaching materials used. The participants could present the results of group reflections and carry out simple fact checks.